2000
DOI: 10.1002/1529-0131(200004)43:4<720::aid-anr2>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Report on the fourth International workshop on reactive arthritis

Abstract: There are large differences in the antigenicity and biology of the ReA-associated bacteria. For induction of arthritis, the relevance seems to be only that antigenic material reaches the joint, alive or dead. If there is a common antigen, it has to be a highly conserved one. Bacterial hsp60 seems to be an immunodominant T cell antigen in ReA, but there must be other relevant antigens shared by these different bacteria. An ineffective immune response (for example, low production of TNFalpha) seems to contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
1
5

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 47 publications
(54 reference statements)
0
69
1
5
Order By: Relevance
“…A similar time course was observed for the induction of immunoprotection by CpG ODNs in mice (18)(19)(20)28,29): protection generally developed several days after administration and persisted for 1-2 weeks (depending upon the pathogen). A longer delay is typical for the development of reactive arthritis in humans following bacterial infection (2,3). The delayed kinetics may reflect differences in the exposure to DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar time course was observed for the induction of immunoprotection by CpG ODNs in mice (18)(19)(20)28,29): protection generally developed several days after administration and persisted for 1-2 weeks (depending upon the pathogen). A longer delay is typical for the development of reactive arthritis in humans following bacterial infection (2,3). The delayed kinetics may reflect differences in the exposure to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive arthritis presents as an asymmetric oligoarticular inflammatory condition that typically appears 1-3 weeks after microbial infection of the gastrointestinal or genitourinary tract (1,2). Bacterial DNA, but not viable microorganisms, can be found in the affected joints, suggesting that DNA may trigger or contribute to this inflammatory process (1,3,4).…”
mentioning
confidence: 99%
“…Therefore, only these pathogens will be discussed, but similar conclusions can be drawn for other bacteria if the respective data are available. The prevalence of infections with these bacteria certainly differs between countries and even between areas in the same country and might also change over time (20). Therefore, the examples given below have to be adjusted to the local conditions.…”
Section: Bacteria Triggering Reamentioning
confidence: 99%
“…However, DNA of these bacteria is only rarely detected inside the joint, and it has been suggested that, instead, mucosa and lymph nodes might serve as a reservoir for Yersinia and Salmonella (for discussion, see ref. 20). Therefore, a Salmonella-or Yersinia-specific PCR for joint material does not currently play a role in the diagnosis of ReA.…”
Section: Bacteria Triggering Reamentioning
confidence: 99%
See 1 more Smart Citation